If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(8x + 9) = 4 + -5x Reorder the terms: 3x(9 + 8x) = 4 + -5x (9 * 3x + 8x * 3x) = 4 + -5x (27x + 24x2) = 4 + -5x Solving 27x + 24x2 = 4 + -5x Solving for variable 'x'. Reorder the terms: -4 + 27x + 5x + 24x2 = 4 + -5x + -4 + 5x Combine like terms: 27x + 5x = 32x -4 + 32x + 24x2 = 4 + -5x + -4 + 5x Reorder the terms: -4 + 32x + 24x2 = 4 + -4 + -5x + 5x Combine like terms: 4 + -4 = 0 -4 + 32x + 24x2 = 0 + -5x + 5x -4 + 32x + 24x2 = -5x + 5x Combine like terms: -5x + 5x = 0 -4 + 32x + 24x2 = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-1 + 8x + 6x2) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-1 + 8x + 6x2)' equal to zero and attempt to solve: Simplifying -1 + 8x + 6x2 = 0 Solving -1 + 8x + 6x2 = 0 Begin completing the square. Divide all terms by 6 the coefficient of the squared term: Divide each side by '6'. -0.1666666667 + 1.333333333x + x2 = 0 Move the constant term to the right: Add '0.1666666667' to each side of the equation. -0.1666666667 + 1.333333333x + 0.1666666667 + x2 = 0 + 0.1666666667 Reorder the terms: -0.1666666667 + 0.1666666667 + 1.333333333x + x2 = 0 + 0.1666666667 Combine like terms: -0.1666666667 + 0.1666666667 = 0.0000000000 0.0000000000 + 1.333333333x + x2 = 0 + 0.1666666667 1.333333333x + x2 = 0 + 0.1666666667 Combine like terms: 0 + 0.1666666667 = 0.1666666667 1.333333333x + x2 = 0.1666666667 The x term is 1.333333333x. Take half its coefficient (0.6666666665). Square it (0.4444444442) and add it to both sides. Add '0.4444444442' to each side of the equation. 1.333333333x + 0.4444444442 + x2 = 0.1666666667 + 0.4444444442 Reorder the terms: 0.4444444442 + 1.333333333x + x2 = 0.1666666667 + 0.4444444442 Combine like terms: 0.1666666667 + 0.4444444442 = 0.6111111109 0.4444444442 + 1.333333333x + x2 = 0.6111111109 Factor a perfect square on the left side: (x + 0.6666666665)(x + 0.6666666665) = 0.6111111109 Calculate the square root of the right side: 0.78173596 Break this problem into two subproblems by setting (x + 0.6666666665) equal to 0.78173596 and -0.78173596.Subproblem 1
x + 0.6666666665 = 0.78173596 Simplifying x + 0.6666666665 = 0.78173596 Reorder the terms: 0.6666666665 + x = 0.78173596 Solving 0.6666666665 + x = 0.78173596 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6666666665' to each side of the equation. 0.6666666665 + -0.6666666665 + x = 0.78173596 + -0.6666666665 Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000 0.0000000000 + x = 0.78173596 + -0.6666666665 x = 0.78173596 + -0.6666666665 Combine like terms: 0.78173596 + -0.6666666665 = 0.1150692935 x = 0.1150692935 Simplifying x = 0.1150692935Subproblem 2
x + 0.6666666665 = -0.78173596 Simplifying x + 0.6666666665 = -0.78173596 Reorder the terms: 0.6666666665 + x = -0.78173596 Solving 0.6666666665 + x = -0.78173596 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6666666665' to each side of the equation. 0.6666666665 + -0.6666666665 + x = -0.78173596 + -0.6666666665 Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000 0.0000000000 + x = -0.78173596 + -0.6666666665 x = -0.78173596 + -0.6666666665 Combine like terms: -0.78173596 + -0.6666666665 = -1.4484026265 x = -1.4484026265 Simplifying x = -1.4484026265Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.1150692935, -1.4484026265}Solution
x = {0.1150692935, -1.4484026265}
| 4x=-40 | | 6x^2-x-1=1 | | -2x-11=-31 | | (x-4)-3=11 | | 2(x-1)=4x-12 | | 11x-(x-20)=100 | | 16x^2=80 | | X-(4-x)=20 | | 6x-14=2x-2 | | 2x^2+5x=5 | | x-4=5-2x | | 14x-4=13x | | 3x-9=12x | | 15(t-6)+6t=7(3t+2)-8 | | 3x+60=2x | | 3x+60=2n | | 9x-11x=20 | | -.16666(x-18)+.5(x+2)=x+4 | | .3(x+7)-.5(x+1)=-6 | | X^2-x=72 | | 7y-5=4y+10 | | .333(x+7)-.5(x+1)=-6 | | 81x=63 | | 5x-4x=5-3 | | 2x-5y=251 | | x^2-2=-2x^2+5x | | -(5y+3)-(-4y-8)=-3 | | .333x+2.3-.5x+.5=-6 | | -5n+16=-7n | | 2x+5y=251 | | 2x-8=4x+2 | | 5r+5=40r+10 |